1996
DOI: 10.1103/physrevlett.77.207
|View full text |Cite
|
Sign up to set email alerts
|

Perturbative Expansion for Coherence Loss

Abstract: We construct a generally applicable short-time perturbative expansion for coherence loss. Successive terms of this expansion yield characteristic times for decorrelation processes involving successive powers of the Hamiltonian. The second order results are sufficient to precisely reproduce expressions for "decoherence times" obtained in the literature by much more involved and indirect methods. Examples illustrating the influence of initial conditions and the need to evaluate higher order terms are given in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 18 publications
4
105
0
Order By: Relevance
“…Perturbative treatments have proved to very useful in understanding decoherence dynamics [8,12,13,14]. Here, to analytically examine classical vs. quantum intrinsic decoherence dynamics at early times, we apply the perturbative approach developed in our previous work [8] to the case of intrinsic decoherence dynamics.…”
Section: Early-time Intrinsic Decoherence Dynamicsmentioning
confidence: 99%
“…Perturbative treatments have proved to very useful in understanding decoherence dynamics [8,12,13,14]. Here, to analytically examine classical vs. quantum intrinsic decoherence dynamics at early times, we apply the perturbative approach developed in our previous work [8] to the case of intrinsic decoherence dynamics.…”
Section: Early-time Intrinsic Decoherence Dynamicsmentioning
confidence: 99%
“…Meanwhile, it has shown that the initial entangled state can be deduced from the nonstationary autocorrelation function which in consistent with the present system [32]. To do so we use the purity as defined before [33][34][35]. This is an important physical quantity, related to both information content and to thermodynamic behavior which is defined by [36] …”
Section: Linear Entropymentioning
confidence: 99%
“…, the decoherence time deduced from the idempotency defect of the reduced density operator of the cavity field, as suggested in [12], is given by…”
Section: Time-dependent Invariantsmentioning
confidence: 99%